(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Determine the prevalence of hypertension and analyzing some factors related to hypertension in people ≥ 45 years old in Tam Dao district, Vinh Phuc province, in 2024. Method: A cross-sectional descriptive study design. Results: A cross-sectional study on 305 subjects in Tam Dao district, Vinh Phuc province in 2024 showed that the prevalence of hypertension in people ≥ 45 years old was quite high (31.1%), in which the prevalence of hypertension in men (31.8%) is higher than in women (30.4%). The rate of hypertension in the age group over 55 years old is 44.2%, in the age group 45-54 years old it is 29%. The rate of hypertension in the San Diu ethnic group is 79.8%, in the Kinh ethnic it is 9.5%. Grade I hypertension is predominant (65.3%), grade II and III hypertension accounts for 33.7%. Age group; ethnic; eat fruits and vegetables; smoke; overweight and obesity are associated with hypertension with ORs of: 0.52; 0.49; 2.02; 1.75; 0.46 Conclusions: It is necessary to strengthen hypertension screening efforts and develop community-based interventions to change risk behaviors in Tam Dao district, Vinh Phuc province.